SSU rRNA Phylogeny of Arcellinida (Amoebozoa) Reveals that the Largest Arcellinid Genus, Difflugia Leclerc 1815, is not Monophyletic - Gomaa, Fatma; Todorov, Milcho; Heger, Thierry J.; Mitchell, Edward; Lara, Enrique (My University, 2012)
The systematics of lobose testate amoebae (Arcellinida), a diverse group of shelled free-living unicellular eukaryotes, is still mostly based on morphological criteria such as shell shape and composition. Few molecular phylogenetic studies have been performed on these organisms to date, and their phylogeny suffers from typical under-sampling artefacts, resulting in a still mostly unresolved tree. In order to clarify the phylogenetic relationships among arcellinid testate amoebae at the inter-generic and inter-specific level, and to evaluate the validity of the criteria used for taxonomy, we amplified and sequenced the SSU rRNA gene of nine taxa - Difflugia bacillariarum, D. hiraethogii, D. acuminata, D. lanceolata, D. achlora, Bullinularia gracilis, Netzelia oviformis, Physochila griseola and Cryptodifflugia oviformis. Our results, combined with existing data demonstrate the following: 1) Most arcellinids are divided into two major clades, 2) the genus Difflugia is not monophyletic, and the genera Netzelia and Arcella are closely related, and 3) Cryptodifflugia branches at the base of the Arcellinida clade. These results contradict the traditional taxonomy based on shell composition, and emphasize the importance of general shell shape in the taxonomy of arcellinid testate amoebae. (C) 2012 Elsevier GmbH. All rights reserved.